2002
DOI: 10.1108/02651330210451962
|View full text |Cite
|
Sign up to set email alerts
|

Globalization and reluctant buyers

Abstract: This study attempted to empirically test a debatable hypothesis that globalization entails homogenization in consumers’ mind and behavior. Using samples from two countries (USA, n = 120 and Korea, n= 128), this study explored a path model centered on consumers’ reluctance to purchase foreign goods. The findings indicated that, in the US sample only, consumer ethnocentrism plays a mediating role between global openness and the reluctance to buy, although it is on the decrease with the increasing level of global… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
138
2
6

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(158 citation statements)
references
References 26 publications
12
138
2
6
Order By: Relevance
“…For example, in a study involving American and Japanese consumers, Gurhan-Canli and Maheswaran (2000a) found that the cultural value of individualism/collectivism significantly explains COO perceptions. Similar findings were reported by Suh and Kwan (2002) with American and South Korean respondents. As discussed earlier, Canadians are much more individualistic than Moroccans and Taiwanese.…”
Section: Country-of-origin Evaluationssupporting
confidence: 90%
“…For example, in a study involving American and Japanese consumers, Gurhan-Canli and Maheswaran (2000a) found that the cultural value of individualism/collectivism significantly explains COO perceptions. Similar findings were reported by Suh and Kwan (2002) with American and South Korean respondents. As discussed earlier, Canadians are much more individualistic than Moroccans and Taiwanese.…”
Section: Country-of-origin Evaluationssupporting
confidence: 90%
“…Therefore, evaluations and buying intentions of such consumers are influenced by consumer ethnocentrism. This conclusion has pointed out in some particular research for example ethnocentrism of American consumers influence to buying intentions to buy foreign-made automobiles [26] or studies with Portuguese and Korean consumers showed that ethnocentrism increases the rejection of foreign products and enhances the purchase intentions towards domestic products [10,28]. Studies showed that consumers prefer to buy domestic products rather than foreign imports as a consequence of their ethnocentrism.…”
Section: Consumer Ethnocentrismmentioning
confidence: 92%
“…It was found that ethnocentric consumers tend to avoid buying products from any foreign country [2,10,25,26,28]. Therefore, evaluations and buying intentions of such consumers are influenced by consumer ethnocentrism.…”
Section: Consumer Ethnocentrismmentioning
confidence: 99%
“…This is supported from research in developed countries (Baughn & Yaprak, 1996;Sharma et al, 1995). However, other research in developing countries has suggested that the relationship is non-significant and that the two constructs are distinct (Suh & Kwon, 2002;Vida & Reardon, 2008). According to these findings, it is possible for consumers in developing countries to be both patriotic about the home country and curious about foreign cultures (Strizhakova et al, 2008).…”
Section: Consumer Ethnocentrism In Developed and Developing Countriesmentioning
confidence: 81%